Advancing vocational education with VocAR-Flip: Improving student’s comprehension in the digital era - Danny Meirawan; Sri Rahayu; Muktiarni Muktiarni; Zahra Ghinaya; Zenita Sabitri; Affero Ismail (Universitas Negeri Padang, 2025)
In the 21st century, globalization and digital transformation significantly changed patterns of life, including the education sector in Indonesia. Vocational schools were expected to prepare students to compete in the global market; however, they continued to encounter challenges in improving the quality and relevance of learning. This study aimed to develop and evaluate flipbook-based learning media integrated with Augmented Reality (AR) to strengthen students’ engagement, conceptual understanding, and readiness for the digital era. The research employed a pre-experimental method with a one-group pretest–posttest design involving 149 vocational school students in West Java. Data analysis showed that the application of the VocAR-Flip model resulted in an N-gain score of 74.3%, which indicated a high level of effectiveness in improving students’ academic achievement and conceptual understanding. The novelty of this research lies in combining the practicality of flipbook media with the immersive features of AR, producing an interactive learning model that had not been widely applied in vocational education in Indonesia. The findings contribute to the advancement of educational technology by offering an innovative and scalable model that supports Industry 4.0 skills. Furthermore, this research provides benefits for policy reference by highlighting the need to integrate AR-based learning media into vocational school curricula to enhance competitiveness in the global workforce.